Răspunsuri la întrebare
Răspuns de
0
x - y = 3 si xy = - 2
x³ - y³ = ( x - y ) · ( x² + xy + y² ) = 3 · ( x² - 2 + y ² ) =3· ( 5 - 2 ) =3·3 =9
(x -y ) ² = 3 ²
x² - 2xy + y² = 9
x² + y² = 9 + 2xy = 9 + 2 · ( -2) = 9 - 4 = 5
x³ - y³ = ( x - y ) · ( x² + xy + y² ) = 3 · ( x² - 2 + y ² ) =3· ( 5 - 2 ) =3·3 =9
(x -y ) ² = 3 ²
x² - 2xy + y² = 9
x² + y² = 9 + 2xy = 9 + 2 · ( -2) = 9 - 4 = 5
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
10 ani în urmă